Benign Inflammatory Lesion Mimicking Malignancy “Kimura’s Disease”: A Case Report - Putu Erika Paskarani; Luh Ayu Widayanti; Anak Agung Ayu Ngurah Susraini; Herman Saputra; Ni Putu Sriwidyani (National Cancer Center - Dharmais Cancer Hospital, 2020)
Introduction: Kimura’s disease (KD) in Indonesia is quite rare. It is a distinct benign reactive process; however, it is usually mimicking malignancy. It usually affects young adults with a peak incidence in three decades, and men are mostly affected compared to women with a 3:1 ratio. KD is a chronic inflammatory disorder characterized by lymphoid hyperplasia, eosinophilia, and associated with soft tissue swelling that usually arises in head and neck regions with regional lymphadenopathy.Case Presentation: Herein, we report a case in a 55-year-old man from East Indonesia who presented a huge lump on his left head and neck regions. The lump started about 8 years ago. Physical examination found a tumor mass of 20 x 10 cm with indistinct border and multiple lymphadenopathies left coli with the biggest size of 1.3 x 0.7 x 0.5 cm. Peripheral blood examination shows marked eosinophilia. Nasopharyngeal CT scan revealed soft tissue masses and multiple lymphadenopathies suspected of malignancy; however, thorax plain radiology did not show any sign of metastatic process. Histopathological examination shows reactive follicular proliferation, extensive eosinophilia, focal area Folliculolysis, and polykaryocytes of the WarthinFinkeldey type.Conclusion: Based on a complete history, laboratory findings, and histopathological examination, this case is concluded as Kimura’s disease. Although clinical findings and radiological examination suspected it as malignancy, those discrepancies were confirmed as a benign lesion by specific histopathological and laboratory findings. Commonly, most patients have a favorable prognosis and good response to therapy.